Keeping children safe: a multicentre programme of research to increase the evidence base for preventing unintentional injuries in the home in the under-fives - Kendrick, Denise; Ablewhite, Joanne; Achana, Felix; Benford, Penny; Clacy, Rose; Coffey, Frank; Cooper, Nicola; Coupland, Carol; Deave, Toity; Goodenough, Trudy; Hawkins, Adrian; Hayes, Mike; et al. (NIHR Journals Library, 2017)
Background: Unintentional injuries among 0- to 4-year-olds are a major public health problem incurring substantial NHS, individual and societal costs. However, evidence on the effectiveness and cost-effectiveness of preventative interventions is lacking.